Advanced analysis of spatiotemporal behaviors of modal structures and couplings for plasma tomography - Kotaro Yamasaki; Akihide Fujisawa; Yoshihiko Nagashima; Chanho Moon; Yusuke Kosuga; Makoto Sasaki; Daiki Nishimura; Taiki Kobayashi; Yuichi Kawachi; Shigeru Inagaki; Naohiro Kasuya; Takuma Yamada (Scientific Reports)
Abstract Advanced methods, based on the Fourier-Rectangular Function (FRF) series expansion (K. Yamasaki et al., J.Appl. Phys. 126 043304 (2019)), are proposed to analyse plasma images obtained with tomography. The method is applied to images of the entire cross-section of a cylindrical plasma that is dominated by an oscillatory state. The oscillations are characterized by an azimuthal mode of m = 4 (mother mode), whose spatial pattern is modulated by producing child modes (m = 3 and m = 5) through the nonlinear coupling with m = 1 mode (father mode). The proposed methods identify the spatiotemporal properties of the modes and their nonlinear coupling propagation along the amplitude trajectory of the father mode. Here, we report the newly developed analysis methods for tomography images and their capabilities to uncover underlying processes in the oscillatory state of turbulent plasmas.